ANALISIS PENDAPATAN MUDHARABAH MUQAYYADAH DAN NON PERFORMING FINANCING (NPF) TERHADAP PROFITABILITAS (ROA) - Dodi Supriyanto; Dede A. Ardiansah (Universitas Galuh, 2019)
Muqayyadah's Mudharabah Income is significant and non-performing financing (NPF) fluctuates giving effect or impact on the level of profitability (ROA). Purpose of this research is to examine of the impact of Mudharabah Muqayyadah income and Non Performing Financing (NPF) on Profitability (ROA) at PT. Bank Syariah Mandiri, Tbk in the 2012-2016 period both partially and simultaneously. The data used in this study is secondary data which uses quarterly financial statements. The research method used is descriptive and verification method with the analysis of Classical Assumption Test consisting of Normality Test, Autocorrelation Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Analysis Test, Correlation Coefficient Test, Determination Coefficient Test and testing using Partial Test (t Test ) and Simultaneous Test (Test F). The results of this study partially show that Muqayyadah Mudharabah Income has no significant effect on Profitability (ROA) and Non Performing Financing (NPF) which have a significant effect on Profitability (ROA). Then simultaneously Muqayyadah Mudharabah Income and Non Performing Financing (NPF) have a significant effect on Profitability (ROA). The coefficient of determination of Muqayyadah Mudharabah Income and Non Performing Financing (NPF) has an effect of 84.9% on profitability (ROA) while the remaining 15.1% is influenced by other variables not examined by the author.